Consumer confidence and consumers' preferences for infant formulas in China - Sai-wei LI; Chen ZHU; Qi-hui CHEN; Yu-mei LIU (Journal of Integrative Agriculture, 2019)
A series of safety incidents related to domestically-produced infant formulas (DIFs) almost destroyed Chinese consumer confidence in domestic dairy products. Understanding consumer confidence and its effect on consumption behavior is important to restore consumer confidence and enhance the competitiveness of domestic dairy industry. This article first measures Chinese consumer confidence in DIFs safety using a two-dimension scale (optimism and pessimism) and then investigates its effect on consumers' preferences for DIFs through a choice experiment. Involving 450 consumers residing in Beijing, Tianjin and Shijiazhuang, the experiment elicited information on their preferences for DIFs with six attributes (organic raw milk, farm-to-table traceability, region of origin, quality certification, animal welfare, and price). Our analysis yields four findings. First, Chinese consumers still lack confidence in DIFs safety. Second, quality certification is the most preferred product characteristic, followed by organic raw milk and farm-to-table traceability. Third, serving as a signal of high quality, price exerts a positive impact on choices of DIFs for pessimistic consumers. Finally, consumer preferences for farm-to-table traceability and region of origin are significantly influenced by consumer confidence.